Fisheries Social Structure in the Islands of Biak And Supiori - Kedi Suradisastra (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 1999)
EnglishThe study of fisheries social structure among the coastal communities in Biak-Supiori Islands was conducted using a delineated participatory methodology of Appraisal of Fishery Information Systems. Taking place in five sub-districts (kecamatans), the study revealed ecological condition of 24 fishing spots located by Global Positioning System (GPS Position). Nominal and qualitative information was collected through extensive, semi-structured interviews. The information were analyzed and empirically reconstructed using inductive statistics.The study unveiled that fishery is valued as secondary activity among rural communities in the study areas. Local communities protect their natural resources through enforcement of traditional norms, non-formal style, and legal rules and formal way. Yet, differences occur as a manifestation of various interacting variables. Some of these variables are ecological condition, local rules, the government's project and program, and the way the society enforce their local norms and values. It is also important to record the unnoted non-sociological parameter as intervening variables that affect the performance and social behavior of local fishermen in reacting to particular norms and values.IndonesianPenelitian struktur sosial kegiatan perikanan masyarakat pantai di Pulau Biak dan Supiori dilaksanakan dengan menerapkan metode partisipatif pemahaman sistem informasi perikanan. Pengamatan yang dilakukan di lima lokasi kecamatan mengungkapkan kondisi ekologis 24 lokasi penangkapan ikan yang dideteksi dengan Global Positioning System (GPS Position). Informasi nominal dan kualitatif dihimpun dengan wawancara semi-struktur dan dianalisis dengan teknik rekonstruksi empiris dengan statistik induktif.Hasil pengamatan menunjukkan bahwa kegiatan menangkap ikan dinilai sebagai kegiatan sampingan. Masyarakat lokal melindungi sumber daya mereka secara tradisional nonformal, dan secara legal formal. Keragaman yang terdapat merupakan hasil interaksi berbagai peubah. Beberapa parameter yang berperan antara lain adalah kondisi ekologi, tata aturan dan norma lokal, keberadaan proyek dan program pemerintah, dan cara masyarakat setempat menjalankan norma-norma lokal. Selain itu dirasa perlu untuk mempertimbangkan pengaruh parameter nonsosiologis yang tidak terdeteksi untuk lebih memahami penampilan dan perilaku sosial masyarakat dalam bereaksi terhadap norma dan nilai-nilai tertentu.